An algorithm for fatigue crack growth applied to mixed and biaxial mode loadings - Baptista, Ricardo (2019)
Fatigue is still one of the main concerns when dealing with mechanical components failure. While it is fundamental to experimentally determine the fatigue material behavior using standard specimens, testing large and complex component geometries can be complicated. In these cases, the Finite Element Method can be a cost-effective solution but developing fatigue crack growth models is still a complicated task. In order to solve this problem, an algorithm for automatic crack propagation was developed. Using three different modules, the algorithm can generate a complex Finite Element Method model including a fatigue crack; solve this model considering complex loading conditions, by applying the superposition method; and calculate the fatigue crack propagation rate, using it to update the original model. In order to benchmark this solution two different problems were analyzed, a modified compact tension specimen and a cruciform specimen. By modifying the compact tension specimen hole location and simulating an initial crack, it was possible to understand how mixed mode conditions influence the fatigue crack path. Different load ratios and initial crack directions on the cruciform specimen were analyzed. Increasing the load ratio will increase the crack deflecting angle. The obtain solutions were compared with experimental results, showing good agreement. Therefore the developed algorithm can be used to predict the fatigue crack growth behavior on complex geometries and when different types of loads are applied to the component.